Konseling Agamawan Masa Depan (Studi Layanan Konseling pada Santri dan Frater) - Zaen Musyrifin; Suwari Amalia (Kuras Institute, 2022)
Humans are religious creatures and certainly cannot be separated from religious problems. In this study, the author divides people into two categories, namely someone who is taking religious education as a candidate for a religious leader and someone who does not get an education to become a candidate for a religious leader. In general, people who are pursuing religious education as candidates for religious leaders should be free from religious problems. However, the students and brothers still have various religious, personal, social, study and career problems. This is an interesting thing to research. Thus, the research question posed in this study is What are the problems faced by Santri and Brothers as Candidates for Religious Leaders? And what is the strategy for counseling services for students and brothers as Candidates for Religious Leaders? This study uses a qualitative research approach with research subjects, namely 2 representatives from Islamic Education Institutions and 2 representatives from Christian Education Institutions. The results showed that the Santri and Brothers had various problems, but they were required to solve the problems before guiding the people.